PERANAN SEKOLAH LAPANG DAN UPSUS KEDELAI DALAM PENINGKATAN PRODUKSI KEDELAI DI BLORA - Eny Hari Widowati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
Soybean is a food commodity whose needs are always increasing every year along with the increasing population in Central Java. Soybean production has not been able to meet the needs because the production is still low and soybean is not attractive anymore for farmers. Efforts to increase soybean production through field schools and Soy Special Efforts. The objective of this research is to evaluate the production improvement program for the fulfillment of soybean needs. Research location in Blora Regency in May-August 2016. Methods of data collection by interview method, indept and focussed group discussion. Respondents, farmers, traders and branches of agricultural services throughout Blora Regency. Result: a) Availability of soybean is 6,640,22 ton from average requirement equal to 12.164,49 ton; B) New local soybean is absorbed by 7.52% of total availability. For Seed Requirement to large 5.73%,; For the requirement of processed tofu industry, the raw material composition of local soybean is only 20%, so the local soybean absorption is 1.79%; C) Enhancementof local soybean production is influenced by factors: farmers' interest and selling price of soybean. The fulfillment of soybean requirement through increased the production can be done by a) the use of varieties that have potential for the food processing industry; B) cropping crops planted on the planting sistem II and III by applying technology and price protection for farmers; C) socialization that local soybean raw materials have good quality for processed tofu and fermented soybean.